Dynamically grading cerebral collateral circulation using 3D multi-inversion time arterial spin labeling in ischemic stroke: a comparison with digital subtraction angiography - Kong, Chuili; Feng, Quanzhi; Yang, Tiantian; Qiao, Shuwang; Zhang, Xianchang; Pfeuffer, Josef; Han, Tong (Frontiers in Neurology, 2025)
ObjectiveThis study aims to introduce a novel non-invasive imaging method, 3D multi-inversion time arterial spin labeling (3D mTI-ASL), for grading collateral circulation in patients with acute ischemic stroke (AIS) and to compare its effectiveness with digital subtraction angiography (DSA).MethodsWe analyzed data from 28 patients with unilateral internal carotid artery or middle cerebral artery occlusion who underwent both DSA and 3D mTI-ASL imaging before endovascular treatment. A post-processing pipeline was established to grade collateral flow based on 16 perfusion-weighted images. The agreement between the collateral grades derived from ASL and DSA was evaluated.ResultsStrong interobserver agreement was observed for both DSA (κ = 0.856) and mTI-ASL (κ = 0.849). A moderate level of consistency in collateral grading between 3D mTI-ASL and DSA was noted (κ = 0.568, p < 0.001). This was improved when patients were categorized into poor and good collateral groups within both grading systems (k = 0.781, p < 0.001). Notably, patients with good collaterals (Grades 3–4) had significantly lower admission National Institutes of Health Stroke Scale scores compared to patients with poor collaterals (p < 0.028 for DSA and p < 0.015 for mTI-ASL).ConclusionThe 3D mTI-ASL technique shows promise as a reliable, non-invasive method for assessing collateral circulation in AIS. By simulating DSA-derived grading, it may serve as a complementary tool in clinical decision-making for acute stroke management.